Faktor perbezaan tahap pengetahuan HIV/AIDS dan stigma pelajar GMI dan UKM mengikut tahap pendidikan - Muhammad Ajib Abd Razak; Nasrudin Subhi (Penerbit Universiti Kebangsaan Malaysia, 2016)
HIV /AIDS is a global epidemic problem that is faced by many countries. There is a drastic increase of infection cases in children, youths, adults and elderly. Among students, there is a low level of knowledge that affects the comprehension elasticity based on the educational level which contributes to the increasing stigma among students. The focus of this study is to examine the differences of HIV/AIDS knowledge levels and students' stigma according to their levels of education. This study used HIV Knowledge Questionnaires (HIV-K-Q) version of 45 items and The Berger HIV Stigma Scale version of 40 items. 130 students from UKM and GMI participated in the study. Results showed that there were significant differences in the knowledge levels and stigma of HIV/AIDS between students' educational levels (Diploma level, Bachelor and Masters). The findings can assist educational institutions to develop the awareness of HIV/AIDS knowledge by targeting all levels of students' education. The implementation of various campaigns, talks, and interventions of reducing the stigma should be refined and planned as an annual program.